Unilateral Autologous Breast Reconstruction with Bi-pedicled, Conjoined Deep Inferior Epigastric Perforator Flaps - Seth, Akhil K.; Koolen, Pieter G. L.; Sultan, Steven M.; Lee, Bernard T.; Erhard, Heather A.; Greenspun, David T. (Journal of Reconstructive Microsurgery, 2019)
Background The abdomen remains the most popular and reliable donor site for autologous breast reconstruction. Some patients, however, lack sufficient tissue to recreate an aesthetic breast mound using a single-pedicle, deep inferior epigastric perforator (DIEP) flap, particularly when matching a contralateral native breast. The amount of abdominal skin and/or soft tissue reliably supplied by one vascular pedicle is frequently insufficient to adequately restore the breast skin envelope and “footprint.” This study summarizes our experience with using bipedicled DIEP flaps to improve the aesthetic results of unilateral breast reconstruction in such patients.Methods Consecutive patients undergoing unilateral breast reconstruction with bi-pedicled, conjoined DIEP flaps over a 4-year period were retrospectively reviewed. Primary and secondary flap microvascular anastomoses were performed to the antegrade internal mammary (IM) vessels and to either the retrograde IM vessels or a primary DIEP pedicle side branch, respectively. Clinical characteristics and outcomes were recorded.Results Sixty-three patients underwent immediate (n = 29) or delayed (n = 34) reconstruction, with age and body mass index of 54.1 ± 8.4 years and 26.6 ± 4.7, respectively. Mean follow-up was 14.1 months. Twenty-eight (44.4%) patients received prereconstruction radiation therapy. All patients had preoperative abdominal imaging, including 57 (90.5%) using magnetic resonance angiography. There were no flap losses with three operative interventions for flap salvage.Conclusion Unilateral breast reconstruction with bipedicled, conjoined DIEP flaps is safe and reliable. These procedures can be performed with a complication profile similar to single-pedicle DIEP flaps. The additional skin and soft tissue available with bi-pedicled flaps allows for greater flexibility in matching the shape and projection of a woman's contralateral breast, and in some cases is necessary to achieve an aesthetically acceptable reconstruction. With growing expectations among breast reconstruction patients, conjoined bi-pedicled flaps represent a tool for meeting their reconstructive needs and exceeding the status quo for aesthetic outcomes.
Keywords: deep inferior epigastric perforator; breast reconstruction; stacked; free flap